Falls prevention and balance rehabilitation in multiple sclerosis: a bi-centre randomised controlled trial - Cattaneo, Davide; Rasova, Kamila; Gervasoni, Elisa; Dobrovodská, Gabriela; Montesano, Angelo; Jonsdottir, Johanna (Disability and rehabilitation, 2018)
PURPOSE: People with Multiple Sclerosis (PwMS) have a high incidence of accidental falls that have a potentially detrimental effect on their daily life participation. The effect of balance specific rehabilitation on clinical balance measures and frequency of falls in PwMS was studied. METHOD: A bi-centre randomised rater-blinded controlled trial. Participants in both groups received 20 treatment sessions. Participants in the intervention group received treatment aimed at improving balance and mobility. Participants in the control group received treatments to reduce limitations at activity and body function level. Primary measures were frequency of fallers (>1 fall in two months) and responders (>3 points improvement) at the Berg Balance Scale (BBS). Data was analysed according to an intention to treat approach. RESULTS: One hundred and nineteen participants were randomised. Following treatment frequency of fallers was 22% in the intervention group and 23% in the control group, odds ratio (OR) and (confidence limits): 1.05 (0.41 to 2.77). Responders on the BBS were 28% in the intervention group and 33% in the control group, OR = 0.75 (0.30 to 1.91). At follow up ORs for fallers and responders at BBS were 0.98 (0.48 to 2.01) and 0.79 (0.26 to 2.42), respectively. CONCLUSIONS: Twenty sessions 2-3 times/week of balance specific rehabilitation did not reduce fall frequency nor improve balance suggesting the need for more frequent and challenging interventions. Implications for Rehabilitation Programs for balance rehabilitation can improve balance but their effects in fall prevention are unclear. Twenty treatments sessions 2/3 times per week did not reduced frequency of falls in MS. The comparison with similar studies suggests that higher intensity of practice of highly challenging balance activities appears to be critical to maximizing effectiveness.
Keywords: Accidental Falls; Middle Aged; lidé středního věku; lidé; posturální rovnováha; Female; mužské pohlaví; Multiple Sclerosis; Physical Therapy Modalities; úrazy pádem; Male; techniky fyzikální terapie; roztroušená skleróza; Postural Balance; ženské pohlaví; Humans